CREATING FAST AND SAFE STRUCTURAL DESIGNS AND QUARANTINE STRUCTURES DURING AN EPIDEMIC - Arici, Ayse (International Scientific Journal Vision, 2023)
From the existence of human history to the present day, there have been fractures in societies due to different epidemics and infectious diseases. Especially with the Industrial Revolution, because of the business life in the cities, the need for shelter was also needed and unhealthy living spaces increased and epidemic diseases that caused great destruction in the process were experienced. When the living conditions of individuals with contagious diseases or the onset of epidemics are examined, the close relationship between health, architecture and engineering disciplines draws attention in the context of the need for healthy and safe accommodation and the creation of a healthy and safe workplace environment. Individuals who have to struggle with communicable diseases throughout their lives should design their living spaces and work lives for themselves, their families and the health of the individuals around them, taking precautions for personal care areas and common use areas that will take care of social distance. The first aim of this study is to investigate the importance of social distance when it comes to epidemics and infectious diseases and what measures should be taken to be protected from the dangers that may arise from common areas. By using standard forms and on-site survey method, a questionnaire study was applied to patients who had covid-19, which is one of the epidemic diseases, and to patients who experienced different infectious diseases and their relatives in June and July, August 2022. As a result of the research, determining the deficiencies in the buildings so that the patients with epidemic diseases and contagious diseases do not infect their families, environment and friends in the work environment, with alternative solution suggestions, designing a comfortable accommodation and working area until the patients regain their health and safety, so that they can stay safely and healthily in their surroundings. It has been determined that it will contribute to the revision of existing structures or alternative quarantine structures designs.